Computational Study and Evaluation of Lidocaine and Nitroglycerin Ointment for External Hemorrhoid Treatment - Alshargabi, Arwa; Al-Madhagi, Wafa Mohammed; Alzomor, Abdulkarim Kassem (Indian Journal of Pharmaceutical Education and Research, 2024)
Background and Objectives Hemorrhoids are defined as swollen veins in the anus and lower rectum. Hemorrhoids are a common medical problem and have a negative impact on people’s lives. The drugs that are available on the market are limited, and therefore, the objective of the present research is to develop and evaluate a lidocaine and nitroglycerin ointment combination for enhanced external hemorrhoid treatment. Materials and Methods Five formulations of 0.1% lidocaine and 0.1% nitroglycerin ointments (F1-F5) were developed using hydrocarbon bases (B1 and B2), hydrophilic petrolatum B3, hydrophilic B4, and emulsifying base B5. Different physicochemical parameters were conducted to evaluate the quality of the studied formulations. Results Cracking was observed for F1 and F2 and phase transitions were noticed for F4 and F5. While, the hydrophilic petrolatum base formulation F3 showed the best physical stability up to one month with high uniformity with a drug content of 107.5% and a calibration curve R=0.9999. Docking study confirmed the activity of lidocaine and nitroglycerin towards hemorrhoids through conventional hydrogen bonds with target proteins 6s3a and 6t3w, respectively. F3 was tested by nine patients who suffered from external hemorrhoids for seven days. Patients reported a decrease in hemorrhoid grain sizes with excellent tolerability. Conclusion The developed single formulation of two different drugs, lidocaine and nitroglycerin, has synergistic action and is well-tolerated treatment option for external hemorrhoids, as it not only decreases the hemorrhoid symptoms (pain and itchy) but also eliminates the side effects like headache that arise when the drugs are administered alone.
Keywords: Hemorrhoids; Nitroglycerin; Lidocaine; Formulation; In silico; Physicochemical